Direct and residual effects of compost enriched with mussoorie rock phosphate in wheat (Triticum aestivum) - rice (Oryza sativa) sequence - SHARMA, JAGDEV; SHARMA, C R (The Indian Journal of Agricultural Sciences, 2013)
The direct and residual effects of compost in a wheat (Triticum aestivum L. emend. Fiori & Paol.) - rice (Oryza sativa L.) sequence on crop yield, nutrient uptake and soil parameters were studied during 1992-93 and J 993-94 on an acid alfisol. A compost rich in P and N was prepared by composting mussoorie rock phosphate with fresh cowdung and green lantana (Lantana camara L.) biomass for 90 days in different treatment combinations. Composting increased the solubilized P (water soluble and citric acid soluble), total P (%) and N (%) contents and lowered the C : N ratio. Inoculation of the composting materials with Aspergillus awamori (Nakazawa), a P-solubilizing fungus, further increased the solubilized P content and lowered the C : N ratio. The compost applied @ 5 tonnes/ha (on dry-weight basis) was comparable with single superphosphate (39.3 kg P/ha + 5 tonnes farmyard manure on dry-weight basis) in terms of crop yield, nutrient uptake and nutrient status of the soil.